The international political role of the catholic church dogmas - Milan Veselica (Političke Perspektive)
The paper investigates the political role of the last Catholic dogmas proclaimed (or renewed) in the 19th and the first half of the 20th century: the immaculate conception, the papal primacy and infallibility (ex cathedra), and the assumption of Mary. The paper aims to explain their political role in the concrete international context. The dogmatization of certain church teachings comes as a consequence of socio-political challenges, and the political role of dogmas is interpreted from the perspective of the theoretical concept of norm entrepreneurship and the transnational soft power of religious actors. The historical method was used in the work. However, the presented findings point to the long-term importance of studying the relationship between dogma and politics: in order to expand knowledge about the political behavior of the Roman Catholic Church (scientific salience) and to understand the nature of normative entrepreneurship directed at the global Catholic society in all historical moments (social salience).